Flow Distribution Inside An Air Conditioning Distributor Using FLUENT Simulation - MOSTAFA MOHAMED HEIKAL, RAGHDA MOHAMED (Universiti Teknologi Petronas, 2013)
Flow maldistribution and specifically in distributors has been a major area of study in engineering fluid dynamics. This is due to the abundance of distributors in all engineering process and applications, such as chemical processes, solar collectors, microchannels, heat exchangers, cooling equipment and refrigerant distribution in multi-split type of air conditioner. The literature shows some of the work done on the flow distribution in parallel tubes, ejectors and manifolds, and its effect on the pressure drop as well as the energy losses in the heat exchanger. This study aims at investigating (numerically) the non-uniformity of the flow in various tubes inside the distributor, and trying to solve it using various techniques as well as effect of changing the geometry of the distributor. Using FLUENT 14 software to carry out the CFD study in a one-phase flow (liquid). The results obtained show that the distributor inlet should be long enough in order for the flow to be fully developed. The role of the dispersion cone in making the flow uniform is clearly seen. Also the difference in lengths of the outlet tubes, shows that the short tubes have faster flow and better distribution due to less pressure drop along their lengths. And by changing the outlet tubes diameters the flow distribution became almost uniform throughout all the tubes, which follows the continuity equation.